2021
DOI: 10.1590/s1679-49742021000400010
|View full text |Cite
|
Sign up to set email alerts
|

Cobertura de equipes de saúde bucal na Estratégia Saúde da Família e uso de serviços odontológicos em adolescentes de Mato Grosso do Sul, 2019: estudo transversal

Abstract: Resumo Objetivo Analisar a associação entre a cobertura de equipes de saúde bucal na Estratégia Saúde da Família (ESF-SB) e a utilização de serviços odontológicos entre adolescentes de 12 anos, em Mato Grosso do Sul, Brasil, 2019. Métodos Trata-se de um estudo transversal, cujo desfecho foi a utilização de serviços odontológicos. Modelos de equações estruturais foram construídos para testar a associação das covariáveis com o desfecho. Resultados Dos 615 participantes, 74,0% utilizaram os serviços odontoló… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Because this was cross-sectional data, some limitations must be pointed out. Only data from public schools were collected, which limits the study generalization for all 12year-old adolescents at the state level [4,13]. Concerning the representativeness of the study population, the ve cities are the most representative of the four territorial macro-regions in the State and are the major a uent areas [13,4].As another strength, this machine learning approach would represent better the local level of data and could be applied better in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Because this was cross-sectional data, some limitations must be pointed out. Only data from public schools were collected, which limits the study generalization for all 12year-old adolescents at the state level [4,13]. Concerning the representativeness of the study population, the ve cities are the most representative of the four territorial macro-regions in the State and are the major a uent areas [13,4].As another strength, this machine learning approach would represent better the local level of data and could be applied better in this context.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of use of dental services proved to be regular, since more than half of the children had an appointed with the dentist within 2 years. Despite this, the use of dental services among children was more related to treatment than to prevention, suggesting a need for change in the work process of oral health teams, especially regarding the expansion of prevention and health education, for a model of integral care to child and adolescent health 7 . Another worrying fact is the non-use of dental services, represented by children who sought care but were not seen; this suggests failures in the organization of the local health system.…”
Section: Discussionmentioning
confidence: 99%
“…Another worrying fact is the non-use of dental services, represented by children who sought care but were not seen; this suggests failures in the organization of the local health system. On the other hand, a recent study conducted in Brazil showed an association between greater coverage of oral health teams in the Family Health Strategy (ESF-SB), greater use of dental services in the public network, and the use of services for treatment by 12-year-old children, revealing the influence that contextual factors have on individual choices 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a population‐based cross‐sectional study derived from the epidemiological survey called SBMS 2018/2019 that occurred in the five largest cities in the state of Mato Grosso do Sul (> 80,000 inhabitants), namely: Campo Grande, Dourados, Três Lagoas, Corumbá and Ponta Porã, between April 2018 and February 2019 11 …”
Section: Methodsmentioning
confidence: 99%